Monocyclic and bicyclic monoterpenes in air of German daycare centers and human biomonitoring in visiting children, the LUPE 3 study. - Schmidt, Lukas; Lahrz, Thomas; Kraft, Martin; Göen, Thomas; Fromme, Hermann (Environment international, 2015)
To investigate the assumed association between indoor air pollution with monoterpenes (MTps) and the internal MTp exposure of occupants, a comparative study was performed in daycare centers in two federal states of Germany. Three well-known monoterpenoid air pollutants, viz. α-pinene (αPN), Δ(3)-carene (CRN), and R-limonene (LMN), were measured in indoor air in 45 daycare centers. Additionally, urine samples of 222 children visiting these facilities were collected in the evening after a full-day stay. Altogether 11 MTp metabolites were analyzed in the urine samples using a novel highly sensitive and selective gas chromatographic-tandem-mass spectrometric procedure. The medians (95th percentiles) of the MTp levels in indoor air were 9.1 μg m(-3) (94 μg m(-3)) for LMN, 2.6 μg m(-3) (13 μg m(-3)) for αPN, and <1.0 μg m(-3) (3.2 μg m(-3)) for CRN. None of the day care centers exceeded the German health precaution or hazard guide value. In spite of the low MTp air exposure, the urine analyses revealed an exposure to the three monoterpenes in almost all children. The median levels of MTp metabolites in urine were 0.11 mg L(-1) for LMN-8,9-OH, 0.10 mg L(-1) for LMN-1,2-OH, 49 μg L(-1) for PA, 2.9 μg L(-1) for POH, 5.2 μg L(-1) for tCAR, and 4.1 μg L(-1) for cCAR (LMN metabolites), 7.2 μg L(-1) for MYR, 19 μg L(-1) for tVER, and 19 μg L(-1) for cVER (αPN metabolites), as well as 8.2 μg L(-1) for CRN-10-COOH (CRN metabolite). Statistically significant and strong correlations among the urinary metabolites of each MTp were found. Moreover, statistical associations between LMN metabolites and the LMN indoor air levels were revealed. However, the weakness of the associations indicates a considerable impact of other MTp sources, e.g. diet and consumer products, on the internal exposure.